PRESERVATION OF PHYSICAL AND MENTAL HEALTH OF JUNIOR SCHOOL STUDENTS IN TIME FORMATION OF PERSISTENCE BY MEANS MOVING GAMES - Dikhtyarenko, Z.M. (Pedagogy of Higher and Secondary Education, 2022)
The article deals with the protection o f physical and psychologic health of young pupils by means of mobile games